Developing Baamboozle-Based Learning Media to Enhance Badminton Footwork Techniques for Senior High School Students - Maryatul Qibtiyah; Silvi Aryanti; Wahyu Indra Bayu; Fitri Agung Nanda; Hartati Hartati; Samsul Azhar (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: The use of technology-based learning media in Physical Education, Sports, and Health remains limited, particularly in badminton footwork instructional materials. This limitation affects students’ motivation, engagement, and understanding. Therefore, innovative and interactive learning media are required to support effective learning.Aims: The aim of this research is to develop Baamboozle-based learning media for badminton footwork technique materials for senior high school students and to evaluate its feasibility and examine student responses.Methods: This study employed research and development (R&D) using the ADDIE model with stages of analysis, design, development, implementation, and evaluation. The sample consisted of eleventh-grade students at Rambang Dangku State Senior High School 2. Data were analyzed using percentage analysis techniques.Results: This research resulted in a Baamboozle-based learning media product that was declared highly suitable by experts. Validation results showed a percentage of 86% from material experts, 84% from language experts, and 88.89% from media experts. Teacher responses reached 92.5%, categorized as very interesting. Student responses were 94.58% in minor trials and 93.86% in major trials, both classified as very interesting.Conclusion: The learning media developed using Baamboozle is highly suitable and effective for application in teaching badminton footwork techniques at the high school level and can be an alternative interactive learning medium for physical education subjects.